2019
DOI: 10.1121/1.5099350
|View full text |Cite
|
Sign up to set email alerts
|

Passive ocean acoustic tomography in shallow water

Abstract: It has been demonstrated that an estimate of an empirical Green's function (EGF) can be extracted from the ocean ambient noise cross-correlation functions, which can provide an alternative method for ocean acoustic tomography. However, the requirement for a long recording time to obtain EGFs with a high signal-to-noise ratio limits the application. This article focuses on using array signal processing to accelerate the convergence rate of EGFs between two horizontally separated arrays. With the extracted EGFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…By Equation (11), the second principle to divide the vertical can be summarized: every layer should be divided to include roughly the same ray length to minimize the inversion errors. At the same time, the third principle can be inferred that inversion error decreases as the layer number increases.…”
Section: Comparison Of S2-s3mentioning
confidence: 99%
See 1 more Smart Citation
“…By Equation (11), the second principle to divide the vertical can be summarized: every layer should be divided to include roughly the same ray length to minimize the inversion errors. At the same time, the third principle can be inferred that inversion error decreases as the layer number increases.…”
Section: Comparison Of S2-s3mentioning
confidence: 99%
“…The CAT system developed by the Hiroshima University Acoustic Tomography Group has been widely used for oceanographic observation since 1995 [6]. Plenty of experiments have been conducted to measure depth-averaged water temperature or map temperature distribution vertically and horizontally with the CAT system [7][8][9][10][11][12][13]. Syamsudin et al obtained a five-layer-averaged water temperature and flow velocity of the vertical profile successfully in the Bali Strait using two acoustic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the ocean, ambient noise interferometry has been experimentally demonstrated to estimate the Green's function for a diverse set of environments and illuminating sound sources (Brooks & Gerstoft, 2009;Brown et al, 2014;Fried et al, 2008;F. Li et al, 2019;Ragland, Abadi, & Sabra, 2022;Roux & Kuperman, 2004;).…”
Section: Introductionmentioning
confidence: 99%
“…Its primary objective was to investigate the interaction mechanism between the acoustic field and the water bodies. It is shown that the mutual correlation function and Green's function of marine environmental noise have the similarity of arrival time structure, based on which some scholars proposed the idea of using marine environmental noise for passive acoustic tomography, and the idea was realised by experimental observation (Gasparini et al, 1997;Fried et al, 2013;Li et al, 2019). The presence of mesoscale processes such as ocean fronts/vortices in the oceans has led to the development of acoustic tomography for horizontally varying environmental (Carrière and Hermand, 2008;Yang et al, 2022);.…”
Section: Introductionmentioning
confidence: 99%